PENGARUH JOB INSECURITY DAN STRES KERJA TERHADAP TURNOVER INTENTION KARYAWAN PADA HOTEL ASANA AGUNG PUTRA BALI - Septiari, Ni Ketut; Ardana, I Komang (E-Jurnal Manajemen; Vol 5 No 10 (2016), 2016)
Employee turnover intention is the desire to quit his job which aims to get another job. The purpose of this study was to determine the effect of job insecurity, job stress on employee turnover intetion in Hotel Asana Agung Putra Bali. This research was conducted at the Hotel Asana Agung Putra Bali, the samples taken were 51 people with saturated sampling method, where the method of saturated samples using the whole population of the respondents in the study. The data collection is done by distributing questionnaires using l ikert scale. The analysis technique used is multiple linear regression. The results showed that job insecurity and stress of work simultaneously significant effect on turnover intention. Job insecurity positive and significant impact on employee turnover intention. Work stress and significant positive effect on employee turnover intention. Advice can be given to the hotel management should provide a comfortable work situation and taking into account the responsibilities and authority of employees in the work.
Keywords: job insecurity, job stress, turnover intention